سعر الفائدة من وجهة النظر التقليدية والإسلامية (المجلة العراقية للعلوم الاقتصادية, 2018)
The system or doctrine of Islamic economic system is a special and separate itself from all the systems because the economic situation comes from God, and that the principles and foundations of Islam and can make up the foundations of economic theory. Where the researcher believes that the economic theory in Islam, and the only task of the researcher revealed. From this point of this study was to examine the relationship between the rate of profit and the general level of prices to explain Gibson's paradox from an Islamic perspective . المقدمة: